Barrier height inhomogeneities induced anomaly in thermal sensitivity of Ni/4H-SiC Schottky diode temperature sensor - Kumar, Vibhor; Maan, Anup Singh; Akhtar, Jamil (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures, 2014)
This paper presents the thermal sensitivity variation trend of Ni/4H-nSiC (0001) Schottky diode based temperature sensor, equipped with floating metal guard ring and oxide field plate as edge terminations in low current regime, i.e., ranging from 1 nA to 5 pA. Various measurements were carried out at temperatures ranging from 233 K to 473 K in steps of 20 K. An imperative outcome of the present study, which is in contrast with the theory, is that there exists an anomaly in the device thermal sensitivity behaviour after a range of current. The thermal sensitivity of the fabricated device, calculated from the slope of forward voltage versus temperature plot, was found to be varied from 3.11 mV/K at 1 nA to 3.32 mV/K at 5 pA with standard error of ±0.03 mV/K. A detailed analysis of I-V-T characteristics by taking into account all the possibilities for variation in the barrier height and the ideality factor with temperature emphasizes that there exist barrier height inhomogeneities at the metal–semiconductor interface in the fabricated device. These observations indicate that anomaly in the device thermal sensitivity was due to the barrier height inhomogeneities present in the device.